2012
DOI: 10.1007/s10865-012-9434-0
|View full text |Cite
|
Sign up to set email alerts
|

Couples coping with multiple sclerosis: a dyadic perspective on the roles of mindfulness and acceptance

Abstract: This study investigated the roles of mindfulness and acceptance on adjustment in couples coping with multiple sclerosis (MS) by examining the effects of an individual's mindfulness and acceptance on their own adjustment (actor effects) and the effects of their partner's mindfulness and acceptance on their adjustment (partner effects) using the Actor-Partner Interdependence Model. The study was a cross-sectional standard dyadic design that collected data from couples coping with MS. Sixty-nine couples completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
61
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 66 publications
12
61
0
1
Order By: Relevance
“…The positive association between acceptance and all assessed indexes of quality of life further adds to a growing body of evidence in patients with MS [5,12,26,[33][34][35][36][37] and in other chronic health conditions such as chronic pain [28,29], chronic fatigue syndrome [30,31], and cystic fibrosis [32]. Apparently acceptance is an important predictor in wellbeing in a broad range of chronic health problems, and MS is no exception.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The positive association between acceptance and all assessed indexes of quality of life further adds to a growing body of evidence in patients with MS [5,12,26,[33][34][35][36][37] and in other chronic health conditions such as chronic pain [28,29], chronic fatigue syndrome [30,31], and cystic fibrosis [32]. Apparently acceptance is an important predictor in wellbeing in a broad range of chronic health problems, and MS is no exception.…”
Section: Discussionmentioning
confidence: 87%
“…Research has shown the beneficial effects of acceptance on various measures of wellbeing in a variety of chronic diseases, including chronic pain [28,29] [32] (e.g., Casier et al , 2008). Studies in patients with MS suggest similar associations between acceptance (or acceptance-related concepts such as sense giving) and life satisfaction, distress, mood, disability, and physical health [5,12,26,33,34,35,36,37]. However, its potentially dampening effect upon the impact of MS severity on quality of life remains untested.…”
Section: Introductionmentioning
confidence: 99%
“…4,48 In addition, because MS extends beyond the person diagnosed as having MS, by adding to financial concerns for the family unit and adding possible caretaking responsibilities, the support individuals for people with MS could be included in future Mindfuless in Motion interventions. 23,48 To our knowledge, this study is the first empirical research examining the feasibility of the Mindfulness in Motion program for people with MS, exploring its potential effect on common symptoms of MS, specifically, anxiety, depression, fatigue, and QOL. This study adds to the growing body of research supporting the benefit of mindfulness and yoga in helping people with MS cope with physical, cognitive, and emotional symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…4 Yoga techniques may be useful in decreasing the emotional distress of disease diagnosis and health-related changes. 4,17 Although a variety of studies have shown yoga to be safe and effective for improving physical function and mood states, only a handful of studies to date have been specific to MS and yoga, and only a few others to mindfulness meditation and MS. 4,5,8,[18][19][20][21][22][23][24][25][26][27][28][29] In addition, because MS is thought to be exacerbated by stress, 1 interventions such as yoga and mindfulness-based interventions can help break patterns of excessive worry, rumination, and stress that are linked to depression and anxiety. 4,16,17,[30][31][32] Indeed, in a recent survey of 1110 people with MS, 32% of those who had used mind-body therapies found them to be beneficial.…”
Section: Mindfulness In Motion Interventionmentioning
confidence: 99%
See 1 more Smart Citation